A Rat Model of Human Behavior Provides Evidence of Natural Selection Against Underexpression of Aggressiveness-Related Genes in Humans - Oshchepkov, Dmitry; Ponomarenko, Mikhail; Klimova, Natalya; Chadaeva, Irina; Bragin, Anatoly; Sharypova, Ekaterina; Shikhevich, Svetlana; Kozhemyakina, Rimma (Frontiers in Genetics, 2019)
Aggressiveness is a hereditary behavioral pattern that forms a social hierarchy and affects the individual social rank and accordingly quality and duration of life. Thus, genome-wide studies of human aggressiveness are important. Nonetheless, the aggressiveness-related genome-wide studies have been conducted on animals rather than humans. Recently, in our genome-wide study, we uncovered natural selection against underexpression of human aggressiveness-related genes and proved it using F1 hybrid mice. Simultaneously, this natural selection equally supports two opposing traits in humans (dominance and subordination) as if self-domestication could have happened with its disruptive natural selection. Because there is still not enough scientific evidence that this could happen, here, we verified this natural selection pattern using quantitative PCR and two outbred rat lines (70 generations of artificial selection for aggressiveness or tameness, hereinafter: domestication). We chose seven genes—Cacna2d3, Gad2, Gria2, Mapk1, Nos1, Pomc, and Syn1—over- or underexpression of which corresponds to aggressive or domesticated behavior (in humans or mice) that has the same direction as natural selection. Comparing aggressive male rats with domesticated ones, we found that these genes are overexpressed statistically significantly in the hypothalamus (as a universal behavior regulator), not in the periaqueductal gray, where there was no aggressiveness-related expression of the genes in males. Database STRING showed statistically significant associations of the human genes homologous to these rat genes with long-term depression, circadian entrainment, Alzheimer’s disease, and the central nervous system disorders during chronic IL-6 overexpression. This finding more likely supports positive perspectives of further studies on self-domestication syndromes.